Yolk–Shell CoNi@N-Doped Carbon-CoNi@CNTs for Enhanced Microwave Absorption, Photothermal, Anti-Corrosion, and Antimicrobial Properties - Liang, Qiqin; He, Mukun; Zhan, Beibei; Guo, Hua; Qi, Xiaosi; Qu, Yunpeng; Zhang, Yali; Zhong, Wei; Gu, Junwei (Nano-Micro Letters, 2025)
The previous studies mainly focused on improving microwave absorbing (MA) performances of MA materials. Even so, these designed MA materials were very difficult to be employed in complex and changing environments owing to their single-functionalities. Herein, a combined Prussian blue analogues derived and catalytical chemical vapor deposition strategy was proposed to produce hierarchical cubic sea urchin-like yolk–shell CoNi@N-doped carbon (NC)-CoNi@carbon nanotubes (CNTs) mixed-dimensional multicomponent nanocomposites (MCNCs), which were composed of zero-dimensional CoNi nanoparticles, three-dimensional NC nanocubes and one-dimensional CNTs. Because of good impedance matching and attenuation characteristics, the designed CoNi@NC-CoNi@CNTs mixed-dimensional MCNCs exhibited excellent MA performances, which achieved a minimum reflection loss (RLmin) of −71.70 dB at 2.78 mm and Radar Cross section value of −53.23 dB m2. More importantly, the acquired results demonstrated that CoNi@NC-CoNi@CNTs MCNCs presented excellent photothermal, antimicrobial and anti-corrosion properties owing to their hierarchical cubic sea urchin-like yolk–shell structure, highlighting their potential multifunctional applications. It could be seen that this finding not only presented a generalizable route to produce hierarchical cubic sea urchin-like yolk–shell magnetic NC-CNTs-based mixed-dimensional MCNCs, but also provided an effective strategy to develop multifunctional MCNCs and improve their environmental adaptabilities. Highlights: 1 Hierarchical cubic sea urchin-like yolk-shell CoNi@N-doped carbon (NC)-CoNi@carbon nanotubes (CNTs) mixed-dimensional MCNCs with different CNTs contents could be availably and selectively synthesized. 2 Owing to the generated hierarchical cubic sea urchin like yolk-shell structure, CoNi@NC-CoNi@CNTs display marvelous hydrophobic, corrosion resistance and MA performance. 3 The construction of components and special microstructure make CoNi@NC-CoNi@CNTs MCNCs display terrific photothermal and antimicrobial (e g. only 1 mg·mL-1 concentration, ~84.03% antimicrobial rate) proper ties.